2020
DOI: 10.32861/jssr.68.770.775
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Political Environment on the Performance of Business Process Outsourcing Sector in Kenya

Abstract: The purpose of this study is to establish the influence of the political environment on the performance of the Business Process Outsourcing Sector in Kenya. The study covered all the 118 registered business process outsourcing companies in Kenya. Descriptive and inferential statistics were used in this study. The descriptive results indicate that the political climate in Kenya has not been conducive to the business process outsourcing sector. The inferential results indicated that the political environment had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Public sector bureaucracies significantly impact the quality of the business environment (Belás et al, 2019). A study also found that business process outsourcing (BPO) flourishes in an excellent political environment, making it necessary for leaders to establish a conducive political environment (Nyambura et al, 2020). A study suggested that political connections aid businesses in obtaining timely and efficient regulatory services (Zhang & Guo, 2019).…”
Section: Political Environmentmentioning
confidence: 99%
“…Public sector bureaucracies significantly impact the quality of the business environment (Belás et al, 2019). A study also found that business process outsourcing (BPO) flourishes in an excellent political environment, making it necessary for leaders to establish a conducive political environment (Nyambura et al, 2020). A study suggested that political connections aid businesses in obtaining timely and efficient regulatory services (Zhang & Guo, 2019).…”
Section: Political Environmentmentioning
confidence: 99%